Benchmarking and best practices in industrial service business. - Gunasekaran, A. (Benchmarking: An International Journal: Volume 22, Issue 2., 2015)
This ebook includes eight papers demonstrating different aspects of how businesses are transforming toward offering services and product service combinations. The first four chapters are related to service value creation, maintenance and the use of technology in industrial services. The final four chapters focus on supply chain issues.